FAKTOR YANG MEMENGARUHI PROSPEK USAHA JASA DEALER HONDA TERHADAP KINERJA KEUANGAN PADA PT. MGM DI KOTA AMBON - Ronyldo Tandikura; Fransiska Natalia Ralahallo (Soso-Q : Jurnal Manajemen, 2019)
Building and developing the competitiveness of the company, especially in the business of selling two-wheeled motor vehicles requires a focus on customers, promoting quality, continuous innovation, prioritizing service and speed. All of them aim to create better after-sales and relationship marketing, so that the process of developing and maintaining long-term relationships with customers becomes more harmonious and eventually they will decide to repurchase or use the same services in the future.This study aims to test, first partially, the influence of Relationship Marketing Factors on Profitability; second, partially testing the effect of After Sales Service Factors on Profitability at PT. MGM in Ambon City.This research uses primary and secondary data, and the type of research used is the type of explanatory research with a quantitative approach. The method used in this study is multiple regression analysis using SPSS 20.0 computer program.The results of this study indicate that the first hypothesis is partially positive and significant between relationship marketing to the profitability of PT. MGM in Ambon City with a significance level of 0.05 and a value of Standardized Coefficients of 0.438. Furthermore, the second hypothesis shows that partially or t-test, the significance value of the after-sales service obtained is greater than the significance level of 0.05, with a negative coefficient value of 109. So it can be seen that after-sales service has no significant and negative effect on the profitability of PT. MGM in Ambon City. Keywords: Relationship Marketing Factors, After Sales Service Factors and Profitability of PT. MGM in Ambon City